Magnetic Ground States for Bent Nanotubes - Altbir-Drullinsky, D; Allende-Prieto, S; Castro-Barrera, M; Mancilla-Almonacid, D (Elsevier B.V., 2020)
Magnetic nanotubes have been widely studied because they are promising candidates to be part of devices based on spintronic and magnonic technologies. However, the experimental techniques used to prepare such structures cannot guarantee the generation of perfect elements, and some geometric imperfections can appear. In this direction, the existence of a bent in a nanotube could change the magnetic properties of a device. In this work, we analyze the influence of curvature on the magnetic properties of a bent nanotube. Our results show a strong dependence of the magnetization ground state on the curvature, the thickness, and the length of the bent nanotubes. Also, we obtained the critical thickness where the transition from the so-called in-surface to the vortex state occurs. For thick tubes, we observe the in-surface state, and for thin structures, the vortex configuration is the lowest energy state. These results could be useful for the development of magnetic devices with bent nanotubes. © 2020 Elsevier B.V.